The Use of Image Rotation Media in Improving Oral Expressive Communication of Autistic Children in Special Schools - Utami, Yuni Tanjung; Rahmawati, Euis; Pratama, Toni Yudha; Aprilia, Imas Diana (Journal of ICSAR, 2024)
This study aims to improve the ability of oral language expressive communication in children with autism by using image rotation media in special schools precisely at Special School 01 Serang elementary school level grade 1 totaling one person. This research uses the experimental method with a Single-Subject Research (SSR) Experimental Study approach. Based on the results of the study showed an increase in oral language expressive communication skills. The baseline phase 1 (A1) which was conducted in 4 sessions showed a similar percentage value of 33%. The intervention phase (B) which was carried out in 8 sessions resulted in a percentage value of 79%, 79%, 79%, 85%, 85%, 85%, and 85%. The baseline 2 phase (A2) which was carried out 4 sessions showed a percentage value of 69%, 82%, 82%, and 82%. Effectiveness seen from the overlap percentage, from intervention (B) to baseline 1 (A1) and baseline 2 (A2) to intervention (B) does not show overlapping data. Overall, the use of image rotation media in improving oral language expressive communication skills in autistic children at Special School 01 Serang is effective.